An Overview of Free Space Optics Communication System - Kavitha, S. (IRO Journal on Sustainable Wireless Systems, 2022)
Free space optics is a kind of broadband communication technique that transmits the signals, in the atmosphere through laser beams. In some cases, the laser beams are replaced with infrared and modified beams. Free Space Optics (FSO) is also referred as Free Space Photonics that works same as the principle of fiber optic communication where the source beams are transferred through air medium. In the traditional fiber optic communication, the optical fibers were used for transferring the beam signals. The FSO methodology is widely employed in various ubiquitous applications for their cost and deployment effectiveness. The motive of the work is to explore the concepts and theories behind the operation of different FSO models with their recent progress.
Keywords: Free space communication; hybrid modulation schemes; channel estimation; satellite communication; bandwidth